Pancasila Student Profile Strengthening Project In Growing Entrepreneurial Motivation Of Students - Hanif Ikhwan Asnan (Institut Agama Islam An-Nawawi Purworejo, 2023)
This article examines entrepreneurial motivation through project activities to strengthen the profile of Pancasila students (P5) in the independent curriculum for junior high school students as an essential provision for independent living. This qualitative study aims to describe the implementation of project activities to strengthen the profile of Pancasila students as a way to foster entrepreneurial motivation for students through market day activities. This research approach is phenomenology by analyzing data descriptively. This research was conducted at SMP Muhammadiyah 6 Surakarta for the 2023/2024 academic year with two research subjects, namely the principal and deputy principal for the curriculum section of SMP Muhammadiyah 6 Surakarta. Data collection techniques in this research include observation, interviews and documentation. Observation is observing objects directly using sight, smell, hearing, touch, or taste. The discussions in this research were conducted with the subjects interviewed, who were the principal and deputy principal of SMP Muhammadiyah 6 Surakarta. Documentation consists of two types: documentation guidelines, which contain outlines or categories for which data will be searched, and checklists, which list variables for which data will be collected. The object of this research is SMP Muhammadiyah 6 Surakarta. The research results of the Strengthening Pancasila Student Profile (P5) Project can foster entrepreneurial motivation for students at SMP Muhammadiyah 6 Surakarta.